PERFORMANCE TEST OF DUAL FUEL ENGINE USINGETHANOL DIESEL - Yanuandri Putrasari; Arifin Nur; Aam Muharam (Widyariset, 2013)
Diesel engine is a high thermal-efficient of internal combustion engine. However, the application of diesel engine still depended on fossil fuel. This fuel has limited availability and the effect are also very dangerous especially its emission. Ethanol was used as an alternative fuel to replace fossil based of diesel fuel. The purpose of this work is to explore the performance of the dual fuel engine–ethanol diesel. The performance test was carried out by running the indirect injection engine that modified to direct injection on 1,500 rpm using four types of fuel i.e. diesel fuel, diesel mixed with ethanol2.,5%, 5%, and 10%. The results show that there was an increasing effect of engi inindicated mean effective pressure (IMEP) value and brake specific fuel consumption (bSFC) reduction when the engine was operated using ethanol diesel fuel blends. The emission of hydrocarbon (HC) tends to increase, while the emission of smoke and carbon monoxide (CO) were decreased when the engine was operated using dual fuel–ethanol diesel.